Amandemen Terhadap Pasal 11 Undang - Undang Dasar 1945 Berkaitan Dengan Ratifikasi Perjanjian Internasional: Perspektif Hukum Internasional Dan Hukum Tata Negara - Delfina Gusman; Zimtya Zora (UIR Press, 2021)
Indonesia cannot close eyes that cooperation with other countries is needed .Different interests and the source of the power possessed make the state independent of one another .Cooperation between countries can occurred in agreed to an international agreement .The national interest and public interest broad should be included in International Agreement to other countries , do not get international treaties approved by the government torment the people. Hence , legal basis international treaties in Indonesia must be clear and firmly , to avoid possible in the practice of especially with regard to the ratification of a treaty. Do not get obscurity legal basis cause financial losses for the state especially the people